(2x+1)=(4x-3)

Simple and best practice solution for (2x+1)=(4x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+1)=(4x-3) equation:


Simplifying
(2x + 1) = (4x + -3)

Reorder the terms:
(1 + 2x) = (4x + -3)

Remove parenthesis around (1 + 2x)
1 + 2x = (4x + -3)

Reorder the terms:
1 + 2x = (-3 + 4x)

Remove parenthesis around (-3 + 4x)
1 + 2x = -3 + 4x

Solving
1 + 2x = -3 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
1 + 2x + -4x = -3 + 4x + -4x

Combine like terms: 2x + -4x = -2x
1 + -2x = -3 + 4x + -4x

Combine like terms: 4x + -4x = 0
1 + -2x = -3 + 0
1 + -2x = -3

Add '-1' to each side of the equation.
1 + -1 + -2x = -3 + -1

Combine like terms: 1 + -1 = 0
0 + -2x = -3 + -1
-2x = -3 + -1

Combine like terms: -3 + -1 = -4
-2x = -4

Divide each side by '-2'.
x = 2

Simplifying
x = 2

See similar equations:

| 4(x-1)=6x | | y=-1000x^2+1100x-2.5 | | 4(6-6)=8 | | 4(x-4)=6x | | 3(-1-2)+6(2-4)= | | 9x-6=102 | | 5(x-2)=3(x-3) | | 5(y-4)/3=2y-5 | | 2(x+9)=24 | | 2.22m=4.4 | | -17=0.20n-20 | | -5(b+3)=-7b-1 | | x+25=-3(x-7) | | Y-8.1=20 | | 2w^2+15w+27=0 | | 7m-1=34 | | 6(3x+1)=-6x-18 | | 11h-7=-18 | | 2.5=1.3-r | | 2x-4+1= | | 3.3a=5.5b | | (25+x)(10+x)=1000 | | 9a=25b | | 8x-11=13x+15 | | 8.1-y=20 | | 18-x=(11+x)+3 | | 7x-7=2x-1 | | -2m-1=6m+1 | | 30000*12=x | | x^3-10x-21x=0 | | 4-2.5(x+5)=16 | | 5.8=x-72 |

Equations solver categories